The Use of Generative AI as a Learning Scaffold for Business Email Writing Among Thai First-Jobbers in Bangkok: The Use of Generative AI as a Learning Scaffold for Business Email Writing Among Thai First-Jobbers in Bangkok - Sangsakrit, Sinakarn; Udomkiatsakul, Piyanut (RATANABUTH JOURNAL, 2026)
This study aimed to investigate the current use of artificial intelligence (AI) in writing business English emails among Thai first-jobber employees in Bangkok and to examine the factors influencing their use of AI for business English email writing. Data were collected from 400 Thai first-jobber employees working in Bangkok, with eight participants selected from each of the city’s 50 districts. The data were analyzed using descriptive statistics and multiple regression analysis. The findings revealed that the respondents’ use of generative artificial intelligence as a learning scaffolding tool was at a high level (M = 4.11). Their behavior regarding the use of generative AI for business English email writing was also at a high level (M = 4.21), while their attitudes toward the use of AI for business English email writing were at the highest level (M = 4.56). The results further indicated that all independent variables jointly explained 72.10% of the variance in the use of generative AI as a learning scaffolding tool among the employees (Adjusted R² = .721). Among the examined factors, attitudes toward generative AI were found to be the strongest predictor (β = 0.527, p < .001), followed by generative AI usage behavior (β = 0.401, p < .001). Both factors significantly influenced the use of generative AI as a learning scaffolding tool at the .01 level of statistical significance.